2012
DOI: 10.1111/j.1463-1318.2011.02820.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tibial nerve stimulation for slow transit constipation: a pilot study

Abstract: Percutaneous tibial nerve stimulation has potential as an affordable and minimally invasive treatment for slow transit constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 27 publications
1
38
1
2
Order By: Relevance
“…Its role in managing constipation, however, has not been investigated in detail. The only published study of its effectiveness in constipation reported a success rate of 32% . In contrast the present study had a significantly lower overall success rate of 11.8%.…”
Section: Discussioncontrasting
confidence: 85%
“…Its role in managing constipation, however, has not been investigated in detail. The only published study of its effectiveness in constipation reported a success rate of 32% . In contrast the present study had a significantly lower overall success rate of 11.8%.…”
Section: Discussioncontrasting
confidence: 85%
“…There were no reports of posterior tibial nerve stimulation (PTNS) or pudendal nerve stimulation after radiotherapy or rectal surgery although the former has been reported in many studies to be effective for faecal incontinence . PTNS has also been reported in constipation , with a similar effect to SNS . PTNS is cheap and can be performed as an outpatient procedure and therefore, given the cost of SNS, PTNS should be investigated in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrate variable efficacy of these surgical treatment entities, and morbidity of these procedures is high . Less invasive and potentially reversible procedures such as sacral neuromodulation and tibial nerve stimulation have been disappointing with respect to efficacy . Therefore, exploration of potentially efficacious minimally invasive therapeutic alternatives for refractory constipation is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…7,[10][11][12] Less invasive and potentially reversible procedures such as sacral neuromodulation and tibial nerve stimulation have been disappointing with respect to efficacy. [13][14][15][16][17] Therefore, exploration of potentially efficacious minimally invasive therapeutic alternatives for refractory constipation is warranted.…”
Section: Introductionmentioning
confidence: 99%